A double‐blind randomized controlled trial to assess efficacy of bromocriptine in cirrhotic patients with hepatic parkinsonism. (4th February 2019) - Sahney, Amrish; Sharma, Barjesh Chander; Jindal, Ankur; Anand, Lovkesh; Arora, Vinod; Vijayaraghavan, Rajan; Dhamija, Ravinder Mohan; Kumar, Guresh; Bhardwaj, Ankit; Sarin, Shiv Kumar
Abstract: Background: Parkinsonism like features can be seen in cirrhotics, possibly related to alterations in brain dopamine metabolism, transport and receptor integrity at basal ganglia. Hepatic parkinsonism is often not suspected and only ammonia‐reducing therapies are given to such patients. We investigated the efficacy and safety of bromocriptine, a dopaminergic agent, in patients with hepatic parkinsonism. Patients and Methods: Cirrhotics were screened for the presence of extrapyramidal symptoms and were diagnosed as hepatic parkinsonism if any two of tremor, bradykinesia and/or rigidity were present, supported by MRI brain showing T1 hyperintensities in basal ganglia and substantia nigra. Patients were randomized to receive placebo (Gr A, n = 22) or bromocriptine (Gr B, n = 24) for 12 weeks. Complete, partial and non‐response were defined as 30%, 10%‐30% and <10% reduction, respectively, in Unified Parkinson's Disease Rating Scale motor score. Results: Of 1016 cirrhotics, 50 (4.9%) had hepatic parkinsonism. Patients in two treatment groups were comparable for MELD score, arterial NH3 and frequency of portosystemic shunts. Bromocriptine therapy for 12 weeks resulted in improvement in rigidity, tremors, bradykinesia and gait compared to placebo with complete and partial response in seven vs none (29.1%, 0%, P  < 0.01) and 12 vs one (50%, 4.5%, P  < 0.01) patients. Prolonged and more severe motor symptoms were associated with non‐response to bromocriptine therapy. There were no major side effects in either treatment group. Conclusions: Hepatic parkinsonism is seen in ~5% cirrhotics. Bromocriptine is a safe and effective therapy for these patients and is more effective in mild to moderate hepatic parkinsonism.